The Korean Crisis : What Did We Know and When Did We Know It? What Stress Tests of the Corporate Sector Reveal - Karasulu, Meral (IMF Working Papers; Working Paper, 2006)
The objective of this paper is to provide a retrospective assessment of our ability to have predicted the impact of the 1997 crisis on the Korean corporate sector. We perform some simple stress tests on the aggregate balance sheets and income statements of the corporate sector to determine what could have been foreseen before the onset of the crisis. Our results show that data available in mid-1997 clearly showed that the corporate sector was very sensitive to various shocks, particularly interest rate shocks. Had stress tests been performed at the time, they would have revealed that the corporate sector was highly vulnerable to adverse economic developments. Our findings suggest that close surveillance of corporate sector balance sheets can play a useful role in understanding potential financial vulnerabilities.